Japanese interrogation techniques from prisoners’ perspectives - Wachi, Taeko (Criminal justice and behavior, 2016)
This study examined responses to a self-report questionnaire on interviewing techniques administered to 291 incoming adult male prison inmates across Japan who were convicted of murder, robbery, arson, rape, forcible indecency, or kidnapping. The questionnaire focused on interrogations that led to confessions. Four interview styles (Evidence-confrontational, Relationship-focused, Undifferentiated-high, and Undifferentiated-low) were identified. For prisoners who had already decided to confess before their interrogation, interview styles had no effect on the tendency to confess. However, when prisoners were undecided about confessing or had previously decided to deny allegations, the Relationship-focused and Undifferentiated-high interview styles were associated with confessions. Furthermore, prisoners who experienced Relationship-focused interviews were more likely to provide previously undisclosed information to the police.